PENILAIAN STATUS GIZI DAN PEMERIKSAAN KESEHATAN BALITA WEIGHT FALTERING UNTUK PENCEGAHAN STUNTING - Fairuza, Firda; Setiati, Dita; Fadilah, Tubagus Ferdi; Ningrum, Nathalia; Sari, Meiriani; Aziza, Nia Nurul (Universitas Trisakti, 2025)
Community service activities were carried out in the form of health screening for weight faltering infants under two years old to improve the health and nutritional status of children in Kelurahan Jati Pulo, kecamatan Palmerah. The partner in this activity was the health sub-department in West Jakarta. The location for the activity was chosen because the sub-district is one of the subdistricts with the most stunting findings and was located close to the Trisakti University. The stunting screening for children under five in the work area of the primary health care follows the National Guidelines for Health Services for stunting in primary healthcare facilities. Still, apart from anthropometric examinations, the diagnosis of stunting was made based on anamnesis, physical examination and supporting examinations carried out by a pediatrician. The solution for community service activities was to reduce stunting prevalence and health screening of weight faltering toddler by a pediatrician. The purpose of this service activity was to prevent stunting and optimalization nutritional status by screening children's weight-faltering health so that parents can provide good and proper care for the process of growth and development of children. The benefit of this activity was that parents, especially mothers of infant, know their children's nutritional status and the importance of the First 1000 Days of Life to prevent nutritional problems in toddlers and improve children's health and nutritional status. The expected output of community service activities was through articles published in community service journals and posters.